ENVIRONMENTAL EDUCATION AND ECOTOURISM: THE PERSPECTIVE OF VISITORS IN A BRAZILIAN NATIONAL PARK - Spazziani, M. L. [UNESP] (2019)
The National Parks (NP) have been assuming an important role both for conservation of natural species (and their environments) and to promote rapprochement of the current human population with nature. Ecotourism, understood as responsible travel to natural areas, aiming at preserving the environment and promoting the well-being of the local population, has been one of the ways to make this important task of NP possible. Ecotourism, also, has contributed to promote, through its natural structures and reception, the Environmental Education of the surrounding populations and visitors. Based on this premise, this research investigated the profile, reasons and perspectives of visitors of a NP located in the state of Rio de Janeiro - Brazil, and possible limitations and contributions to environmental awareness. The field survey, carried out in January 2019, was conducted through structured interviews with 62 visitors from the main headquarters of a NP that offers a welcoming structure, ecological diversity and historical importance of vast significance for the country. The data point out the profile of visitation in this NP in the mentioned period (school holidays), but it is evidenced the importance attributed to this space, in particular to the surrounding communities. There are indications of the lack of structure for reception, especially for the work of Ecotourism and Environmental Education.